An EEG investigation of learning and decision making in smokers - Retzler, C.A. (2014)
To improve the efficacy of addiction treatments it is important to understand the learning and behavioural processes involved. The experimental work presented here aims to further our understanding of the behaviour and related brain activity of smokers, using a range of experimental paradigms and Electroencephalographic (EEG) techniques. A range of behavioural tasks adapted from the animal literature for use with humans, were utilised to explore the choices made by smokers and the effect of smoking-related cues on drug-seeking behaviour. Tasks included concurrent choice and variations of the Pavlovian to Instrumental Transfer (PIT) task. EEG data was recorded during these experiments, and analysed using Event Related Potential (ERP) and frequency measures, to identify a neural component related to these effects. Resting EEG data was also collected and analysed to investigate the relationship between EEG frequency measures and individual difference measures.